Dinosaur Bob and his adventures with the family Lazardo - Joyce, William ([New York, N.Y.] : HarperCollinsPublishers, 1995)
While vacationing in Africa, the Lazardo family finds and brings back to America a friendly dinosaur that becomes the talk of the town.
"A Laura Geringer book."
Maps on lining papers.
Reading rainbow book.
520
Keywords: Dinosaurs -- Juvenile fiction; Dinosaurs -- Fiction